The correlation between metacognitive awareness and cognitive learning outcomes based on gender of biology education students - Romi Adiansyah; Astuti Muh. Amin; Ahmad Yani; Dian Safitri (Biosfer: Jurnal Pendidikan Biologi, 2023)
Metacognitive awareness has a significant and complex correlation with cognitive learning outcomes. So far, there have not been many studies investigating the correlation between metacognitive awareness and cognitive learning outcomes based on gender. This research aimed at determining the correlation between metacognitive awareness and cognitive learning outcomes based on the gender of biology education students. The samples of this research were biology education students in the third semester of 2020/2021 academic year. The research samples comprised 104 students consisting of 47 male students and 57 female students. The research instruments were used to collect the data of students’ metacognitive awareness and cognitive learning outcomes. The results of this research showed that metacognitive awareness had a significant correlation with cognitive learning outcomes both in male students and female students. Metacognitive awareness contributed 66.5% towards the cognitive learning outcomes of male students. This number was greater than that in female students, which was only 39.40%. The results of the ANOVA test showed that the correlation between metacognitive awareness and cognitive learning outcomes in male students and in female students was not parallel and not coincide. The results of this research are expected to have effective contributions for educators to continually improve the achievement of learning objectives that emphasize on the development of metacognition and cognition in order to produce competent and quality graduates